Design centered on non-human users: general survey of the non-anthropocentric segment of visual design, product design and service design - Araujo, Gabriella Ribeiro da Silva e (2025)
The professional field of non-human user-centered design represents a paradigm yet to be extensively explored by academia. Premised on the notion that traditional definitions of \"design\" and \"user-entered design\" remain anchored in anthropocentric views of users, this doctoral thesis aims to broaden the theoretical understanding of the design field, which has hitherto been restrictive. Consequently, it seeks to inform the development of products, visual interfaces, and services for these less recognized categories of non-human users. The findings of this research are derived from an extensive survey and systematization of hundreds of notable and diverse instances of visual design, product design, and service design specifically targeting non-human animal users. This culminates in a complex, multidimensional taxonomy. Within this inventory, identified design manifestations for this segment were categorized into 81 design areas (e.g., solutions for hygiene, safety, feeding, entertainment, transportation, health, etc.). These areas intersect with three potential beneficiary types whose interests are addressed: non-human animals, humans, or users from both categories. A key aspect of this classification involved specifying the intended user classes for these design interfaces--whether non-human animals, humans, or both. Methodologically, the research employed diverse data collection techniques and sources. These encompassed systematic internet searches, a review of related literature, brief semi-structured interviews with pet product entrepreneurs and animal handling/behavior specialists, technical visits to museums and events featuring animals and/or products for this user segment, and observations of practical scenarios in veterinary clinics. Analyzing this extensive, diverse, and largely underexplored domain, the study also identified and mapped intrinsic aspects, topics, themes, and issues pertinent to this design segment. This involved examining some of its most characteristic and specific implications, for instance, within functional, ergonomic, semiotic, ethical, aesthetic, historical, pedagogical, and methodological contexts. This panoramic exploration into the realm of design for this understudied user group is expected to illuminate the breadth of this novel conceptual design paradigm, delineating its epistemological nature and constitutive aspects. Furthermore, it aims to underscore the critical need for a deeper understanding of this field, thereby supporting design pedagogy and fostering more sensitive and informed professional practices. Ultimately, this research seeks to benefit society as a whole and, specifically, enhance the well-being of non-human animal users, elevating them to co-participants in design processes within the continuously expanding domain of design.